Preparation of aligned multi-walled BN and B/C/N nanotubular arrays and their characterization using HRTEM, EELS and energy-filtered TEM - Golberg, D; Bando, Y; Mitome, M; Kurashima, K; Sato, T; Grobert, N; Reyes-Reyes, M; Terrones, H; Terrones, M (2002)
Aligned multi-walled nanotubes composed of B/C/N and/or B/N atoms were synthesized by reacting chemical-vapor-deposition-grown C nanotubes or pyrolitically grown CNx nanotubes, boron oxide and nitrogen at 1773-2200 K. We note that by increasing the reacting temperature, the overall B-N content within the tubular assemblies is also enhanced. The nanostructures were studied using high-resolution transmission electron microscopy, spatially resolved energy-filtered TEM (Omega filter) and electron energy loss spectroscopy. An oxidation-driven mechanism of B-N enrichment within the C-based tubular templates has been proposed and verified by the experimental observations. (C) 2002 Elsevier Science B.V. All rights reserved.